Using waste plastic bottles as additive for stone mastic asphalt - Ahmadinia, Esmaeil; Zargar, Majid; Karim, Mohamed Rehan; Abdelaziz, Mahrez; Shafigh, Payam (Elsevier, 2011)
Currently, polymer modified asphalt mixture is a relatively costly mixture for paving roads. One way to reduce the cost of such constructions and rendering them more convenient is by using inexpensive polymers, i.e. waste polymers. The main purpose of this research is to determine the effect of incorporating waste plastic bottles (Polyethylene Terephthalate (PET)) on the engineering properties of stone mastic asphalt (SMA) mixture. The volumetric and mechanical properties of asphalt mixes that include various percentages of PET (0, 2, 4, 6, 8 and 10) were calculated and assessed with laboratory tests. The appropriate amount of PET was found to be 6 by weight of bitumen. The outcomes were statistically analysed and the determination of the significance at certain confidence limits was performed with the two factor variance analysis (ANOVA). Moreover, some studies conducted on polyethylene modified asphalt mixture have also been taken into consideration in this paper. The results show that the addition of PET has a significant positive effect on the properties of SMA and it can promote the re-use of waste material in industry in an environmentally friendly and economical way.